The Metaphor of ”Dog” in Egyptian Arabic Proverbs - Syahreni, Jessica Meilia; Ma'nawi, Arief (Universitas Ahmad Dahlan, 2024)
Proverbs that employ metaphors are deeply rooted in the social and cultural life of a society, often drawing from animals and plants. These proverbs reflect the characteristics and identity of a community while delivering messages in an easily understandable manner. This study examines the metaphor of the